Sosialisasi Program Penanggulangan Korupsi di Tingkat Desa Bagi Forum BPD Menuju Tata Kelola Keuangan Desa Unggulan di Kabupaten Klaten - Arif Julianto Sri Nugroho; Oki Kuntaryanto; M Pujo Darmo; Dandang Setyawanti; Agung Nugroho Jati (Jurnal Pengabdian Masyarakat - PIMAS, 2022)
This community service activity aims to reveal the role of community participation and the efforts made to increase it in order to prevent corruption act through thematic learning of finance and public accounting for BPD Forum. The method of activities used: 1) sosialisation activities, 2) increasing learning skills in literacy public finance accounting and management for village budget. The learning can be use in understanding community in order to prevent corruption for village budget